Reduction of methylphenidate induced anxiety, depression and cognition impairment by various doses of venlafaxine in rat - Majid Motaghinejad; Manijeh Motevalian; Andia Ebrahimzadeh; Setare Farokhi larijani; Zohreh Khajehamedi (International Journal of Preventive Medicine, 2015)
Background: Methylphenidate (MPH) is a neural stimulant agent, which its neurochemical and behavioral effect remain unclear. Venlafaxine is a serotonin-norepinephrine reuptake inhibitor antidepressant, which was used for management of depression and anxiety. In this study, protective effects of venlafaxine on MPH induced anxiety, depression and cognition impairment were investigated. Methods: Forty-eight adult male rats were divided randomly to 5 groups. Group 1, received normal saline (0.2 ml/rat) for 21 days and served as control group. Group 2, received MPH (10 mg/kg) for 21 days. Groups, 3, 4, 5 and 6 concurrently were treated by MPH (10 mg/kg) and venlafaxine at doses of 25, 50, 75 and 100 mg/kg respectively for 21 days. On day 22, elevated plus maze (EPM), open field test (OFT), forced swim test (FST) and tail suspension test (TST) were used to investigate the level of anxiety and depression in animals. In addition, between days 17 and 21, Morris water maze (MWM) was used to evaluate the effect of MPH on spatial learning and memory. Results: MPH caused depression and anxiety in a dose-dependent manner in FST, OFT, EPM and TST, which were significantly different compared with control group. Furthermore, MPH can significantly attenuate the motor activity in OFT. Venlafaxine in all doses can attenuate MPH induced anxiety, depression and motor activity alterations. MPH also can disturb learning and memory in MWM, but venlafaxine did not alter this effect of MPH. Conclusions: We conclude that venlafaxine can be protective in the brain against MPH induced anxiety and depression.